1997
DOI: 10.1111/j.1749-6632.1997.tb48290.x
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Relevance to PTSD

Abstract: Posttraumatic stress disorder or PTSDI is a psychiatric disorder of considerable prevalence and morbidity and can affect persons of any age and ethnic or socioeconomic background.2-10 It is, unfortunately, a far too common outcome of participation in war, affecting 15.2% of Vietnam theater veterans 20 years after the war." Its prevalence may be even higher in inner city communities exposed to compound community trauma. In one small northeastern city, it was found to affect 67% of adolescents frequenting a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 138 publications
0
29
0
1
Order By: Relevance
“…Similarly, greater intellectual sophistication may facilitate the development of personal resources such as educational attainment, occupational achievement, and other socioeconomic factors, which appear to buffer stress impact (Hobfoll, 1989;Ursano, Wheatley, Sledge, Rahe, & Carlson, 1986). Additionally, if exposure to stress is associated with neurobiological alterations, as animal models suggest (see Bremner et al, 1999;Rasmusson & Charney, 1997, for reviews), then higher levels of premilitary intelligence may reflect reduced central system vulnerability to stress. Indirect support for this hypothesis can be found among studies documenting increased psychological symptoms in trauma survivors with a history of brain injury (Chemtob et al, 1998;R.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, greater intellectual sophistication may facilitate the development of personal resources such as educational attainment, occupational achievement, and other socioeconomic factors, which appear to buffer stress impact (Hobfoll, 1989;Ursano, Wheatley, Sledge, Rahe, & Carlson, 1986). Additionally, if exposure to stress is associated with neurobiological alterations, as animal models suggest (see Bremner et al, 1999;Rasmusson & Charney, 1997, for reviews), then higher levels of premilitary intelligence may reflect reduced central system vulnerability to stress. Indirect support for this hypothesis can be found among studies documenting increased psychological symptoms in trauma survivors with a history of brain injury (Chemtob et al, 1998;R.…”
Section: Discussionmentioning
confidence: 99%
“…Bremner et al, 1999;Rasmusson & Charney, 1997) and findings from the psychopathology literature that indicate that preexposure indices of intellectual resources are associated with PTSD diagnosis (Centers for Disease Control Vietnam Experiences Study, 1988;Green et al, 1990;Harel et al, 1988;Kulka et al, 1990;Macklin et al, 1998;Pitman et al, 1991;Sutker et al, 1990), we predicted that neurocognitive and intellectual performances would be independently associated with PTSD severity after controlling statistically for shared variances between the two variable sets.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Altered HPA axis responsiveness may contribute to the sensitized responses PTSD patients experience to innocuous events that are perceived as threatening; that is, PTSD symptoms may develop via a sensitization process involving the HPA axis that causes less intense stressors to be perceived as stronger than they are (Rasmusson and Charney, 1997;Yehuda, 1997). The initial traumatic event activates the stress response, but upon receiving reminders of the trauma or mild but similar stressors, the stress response reactivates.…”
Section: Stress Responsementioning
confidence: 99%
“…Knowledge about the connections between the neurobiological and the therapeutic effects of MDMA is far from complete, but it has been observed that MDMA acutely decreases activity in the left amygdala (Gamma et al 2000). This action is compatible with its reported reduction in fear or defensiveness, and is in contrast to the stimulation of the amygdala observed in animal models of conditioned fear, a state similar to PTSD ( Rasmusson andCharney 1997, Davis andShi 1999).…”
Section: Ptsd and Mdma-assisted Psychotherapymentioning
confidence: 98%